Perceptions of humanization in the professional performance of psychologists in a teaching hospital - Mendes, Matheus Carvalho (2022)
Taking into account how the professional of Psychology conceives the individual and how the guidelines and principles of the humanization policy direct care, it is possible to see an approximation between the psychologist and the humanization construct. Therefore, it is essential to understand how this professional, so important for the implementation of the practice of this policy, understands the meaning of humanization and how they visualize, in their daily lives, their practice in line with this construct. The objective is to access the understanding of Psychology professionals about the concept of humanization, in addition to analyzing the extent to which humanized behaviors include their understanding of the concept, as well as identifying the aspects that favor or not such practice. It is a cross-sectional, descriptive and qualitative research, having as a method the content analysis, from the answers to an interview designed to contemplate the study objectives. It was possible to understand that Psychology professionals have extensive knowledge about the concept of humanization. It was observed that this knowledge goes far beyond what they manage to implement in professional practice. This practice encounters several obstacles to achieving an ideally humanized character, since they proved to be resistant, crossing the daily care. Lesser number of facilitators were identified when compared to hinderers. However, such facilitators proved to be a relevant support for professionals to try, in their daily lives, to overcome the challenges in order to provide humanized and quality care.